Path planning for mobile robots (A comparative study) - ZEGAAR Souheila, Souheila; SAADOUNE Nour Chames Elassil, Nour Chames Elassil; Supervisor :BENTRCIA, Rahima (University of M'sila, 2023)
This thesis presents a comprehensive comparative study on path planning algorithms for mobile robots, focusing on the simulation environment of the Maze Problem. Path planning is a crucial aspect of mobile robot navigation, and selecting the most appropriate algorithm is essential for efficient and robust operation. This research evaluates and compares the performance of several basic search algorithms, including Dijkstra's algorithm, A* algorithm, BFS algorithm, DFS algorithm, and the artificial intelligence method Genetic algorithm. The evaluation is based on multiple evaluation metrics, namely path length, running time, robustness, search path, and time complexity. To ensure a comprehensive analysis, each algorithm is tested in six different scenarios, with each approach executed ten times in each environment. The experimental results provide valuable insights into the strengths and limitations of the algorithms, aiding researchers and practitioners in selecting the most suitable path planning algorithm for mobile robot applications.
Keywords: path planning, mobile robots, maze solving, Dijkstra's algorithm, A*, BFS, DFS, Genetic algorithm.